Profiling human breast epithelial cells using single cell RNA sequencing identifies cell diversity - Quy H. Nguyen (Nature Portfolio, 2018)
Epithelial subpopulations are present in the human breast but how these differentiate or form is unclear. Here, the authors use single-cell RNA sequencing of primary human breast epithelial cells to define previously undescribed luminal, basal epithelial subpopulations and ZEB1-positive basal cells.